(untitled) (INNOVATIVE ECONOMY, 2020)
Deineha I.O. EVALUATION OF OPPORTUNITIES OF EDUCATIONAL MIGRATION FOR DEVELOPMENT OF HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE Purpose. The aim of the article is to summarizing the positive experience of developed countries in attracting foreign students to their system of providing educational services, assessing the saturation of the segment of the national educational market, which is formed by foreign students, as well as developing recommendations for the prospects of its development with the participation of domestic higher education institutions. Methodology of research. In the process of research, the following scientific methods have been used: historical – to assess the saturation of the segment of the national educational market, which is formed by foreign students; synthesis – to identify difficulties and positive moments of adaptation of foreign youth in Ukraine; mathematical statistics – to assess the dynamics of the share of foreign students in higher institutions of primary education at different levels of accreditation. Findings. The value of foreign students in the educational activity of higher educational institutions of Ukraine and the world is evaluated. The emphasis is on the positive and negative aspects of teaching foreigners in Ukraine. The trends of educational migration in the world are considered. Originality. It is determined that the attraction of foreign students to study at higher educational institutions depends not only on the effectiveness of their communication activities, scientific potential and reputation, as well as on the effectiveness of the decisions of local and state authorities. Practical value. Objects of influence on the growth of the share of foreign students in Ukraine have been identified, which allows them to develop programs for their involvement in studies at domestic higher education institutions. Key words: educational migration; educational services; adaptation of foreign students; internationalization of education; recruiting.